2003
DOI: 10.1209/epl/i2003-00481-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical scaling analysis of plant callus growth

Abstract: PACS. 68.35.Ct -Interface structure and roughness. PACS. 68.35.Fx -Diffusion; interface formation. PACS. 89.75.Da -Systems obeying scaling laws.Abstract. -We present experimental results for the dynamical scaling properties of the development of plant calli. We have assayed two different species of plant calli, Brassica oleracea and Brassica rapa, under different growth conditions, and show that their dynamical scalings share a universality class. From a theoretical point of view, we introduce a scaling hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 24 publications
1
26
0
3
Order By: Relevance
“…Galeano et al [18] analyzed dynamic scaling of the growth of plant calli (i.e., cultured plant cells). However, to the best of our knowledge, there have been no studies that have reported dynamic scaling at the whole-plant level.…”
Section: Introductionmentioning
confidence: 99%
“…Galeano et al [18] analyzed dynamic scaling of the growth of plant calli (i.e., cultured plant cells). However, to the best of our knowledge, there have been no studies that have reported dynamic scaling at the whole-plant level.…”
Section: Introductionmentioning
confidence: 99%
“…We have presented a new dynamic scaling ansatz for the global width function valid for systems whose size is increasing in time. This hypothesis must be used in the case when systems size is increasing in time, for example, in many biological problems like cancer tumors and vegetable callus [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…This is a matter of interest in processes involved in wound healing or malignant tumor growth [1,2]. One of these procedures is based upon the dynamic scaling analysis (DSA) of colony fronts [3][4][5][6][7][8][9][10][11][12]. In this approach, the two-dimensional (2D) cell colony front dynamics is characterized through a set of dynamic scaling exponents (α, β, z, the roughness, the growth, and the dynamic exponents, respectively) derived from DSA applied to the colony front profiles and by comparing them with those expected from different complex statistical models [13,14].…”
Section: Introductionmentioning
confidence: 99%